Emerging adults' financial capability: A financial socialization perspective. (31st October 2019) - Marchant, Caroline; Harrison, Tina
Abstract: This exploratory qualitative research uses the United Kingdom as a case study to understand how past and present financial socialization agents have either enhanced or inhibited emerging adults' financial capability in order to highlight potential opportunities for future policy and practice interventions. Three primary socialization agents were identified. The family as trusted primary advisor continues well into adulthood, even where family financial capability may be low. Beyond this, emerging adults only reluctantly engage with their bank, rely on just‐in‐time experiential learning or self‐socialize via diving, often with false confidence, into the internet. Although there are many quantitative studies on financial socialization, this paper fills a gap by taking a deeply qualitative approach showing, for the first time, empirically highlighting the limited number of financial socialization agents through the voices of emerging adults. The findings contradict previous socialization research that suggests parental socialization reduces into adulthood.